PENGARUH PEMBERIAN BANANA ISOTONIC DRINK DAN GOLD STANDARD MINUMAN ISOTONIS TERHADAP STATUS HIDRASI LANJUT USIA DENGAN MELIHAT VOLUME URIN TAMPUNG 24 JAM - , LUCIA PUTRI K.; , dr. Probosuseno, Sp.PD (K-Ger) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Longevity is susceptible to any health problems, one of them is hydration problem. Isotonic drink can be used to improve hydration status. Banana isotonic drink is a natural product of rehydration drink that made from yellow kepok banana flour. Banana Isotonic Drink can provide health benefits to improve the body's hydration in elderly. Objective: To determine the effect of Banana Isotonic Drink and gold standard isotonic drink in the rehydration of the elderly by looking at 24-hour urine volume and determine difference effect of Banana Isotonic Drink and gold standard isotonic drinks. Methods: An experimental clinical trial study using a cross over design. Subjects were observed for 3x24 hours in each test. Each subject was given a drink as much as 1000 ml within 24 hours. Urine that excreted in 24 hours was collected for examination of urine volume production. Washout period between each test is four days. The data is quantitative, analyzed using paired t-test and independent sample t-test. Results: The volume of urine from day to day in the treatment group Banana Isotonic Drink and gold standard isotonic drinks is increasing. Urine volume from day to day in the treatment group Banana Isotonic Drink and gold standard isotonic drinks are not a significantly difference (p> 0.05). There were no significant differences between the treatment of Banana Isotonic Drink and gold standard isotonic drinks (p> 0.05). Conclusion: There was no significant effect in the treatment of Banana Isotonic Drink and gold standard isotonic drink in the hydration status of the elderly by looking at 24-hour urine volume. In addition, there is no significant difference in 24-hour urine volume due to treatment Isotonic Drink Banana and gold standard isotonic drinks. Treatment of Banana Isotonic Drink has the same effect with gold standard isotonic drinks on the hydration status of the elderly.